2014
DOI: 10.15587/2313-8416.2014.31981
|View full text |Cite
|
Sign up to set email alerts
|

Дослідження Впливу Комплексної Добавки «Мальтовин» На Функціональні Властивості Заморожених М'ясних Напівфабрикатів

Abstract: ДОСЛІДЖЕННЯ ВПЛИВУ КОМПЛЕКСНОЇ ДОБАВКИ «МАЛЬТОВИН» НА ФУНКЦІОНАЛЬНІ ВЛАСТИВОСТІ ЗАМОРОЖЕНИХ М'ЯСНИХ НАПІВФАБРИКАТІВ © І. О. Літвінова, О. М. Савінок В статті наведені дослідження впливу поліфенольної добавки «Мальтовин» на функціональні показники заморожених рубаних напівфабрикатів вироблених за різними технологіями. Аналіз отриманих експериментальних даних дозволяє зробити висновок, що використання комплексної добавки в кількості 2 % до маси сировини затримує окиснення ліпідів і сприяє виробництву продукції в… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Today the effectiveness of different types of anti-oxidizing preparations of a natural origin, caused by the high content of flavonoids and other biologically active compounds, is proved [12][13][14][15][16][17][18][19]. Vegetable antioxidants have the essential potential for the use in the meat products technology, but their introduction has certain limitations because of absence of data about the effectiveness in different types of meat raw material [20][21][22][23][24][25].…”
Section: Food Science and Technologymentioning
confidence: 99%
“…Today the effectiveness of different types of anti-oxidizing preparations of a natural origin, caused by the high content of flavonoids and other biologically active compounds, is proved [12][13][14][15][16][17][18][19]. Vegetable antioxidants have the essential potential for the use in the meat products technology, but their introduction has certain limitations because of absence of data about the effectiveness in different types of meat raw material [20][21][22][23][24][25].…”
Section: Food Science and Technologymentioning
confidence: 99%
“…The authors of [18,19] developed a polyfunctional additive Maltovin. It is based on the extract of polyphenolic compounds of grape seeds and maltodextrin as a carrier of biologically active compounds.…”
Section: Analysis Of the Influence Of Rosemary And Grape Seed Extractmentioning
confidence: 99%
“…Investigation of the influence of Maltovin on the functional and technological properties of minced meat has shown that the additive Maltovin exhibits high functional properties necessary for the production of meat products (especially for chopped semi-finished products). In addition to improving the functional characteristics of products, Maltovin prolongs the shelf life of fat-containing products due to antioxidant properties [18,19].…”
Section: Analysis Of the Influence Of Rosemary And Grape Seed Extractmentioning
confidence: 99%